Vitreous D-Lactate Levels as a Biomarker in the Diagnosis of Presumed Infectious Culture Negative Endophthalmitis. (1st February 2020) - Naik, Poonam; Singh, Sukhvinder; Dave, Vivek Pravin; Ali, Mohammad Hasnat; Kumar, Ashok; Joseph, Joveeta
ABSTRACT: Purpose : Microbiological investigations of vitreous fluid have often failed to detect the causative agent in infectious endophthalmitis resulting in a clinical dilemma. D-Lactate is a byproduct of bacterial metabolism, and its accumulation in sterile body fluids indicates bacterial infection. The aim of the study was to evaluate the measurement of vitreous fluid D-lactate for the diagnosis of infectious endophthalmitis and to define an optimal D-lactate concentration for the differentiation from non-infectious samples. Methods : Vitreous samples of 41 patients clinically diagnosed as endophthalmitis and 20 patients with non-infectious disorders, as controls, between October 2018 and February 2019 were included in the study. D-lactate levels were determined by a D-lactate colorimetric assay kit (MAK058 Sigma-Aldrich) and the receiver operating characteristic curves (ROC) of D-lactate were calculated. The clinical finding of D-lactate production in bacterial endophthalmitis was also verified in a mouse model of bacterial endophthalmitis. Results : Of the 41 patients included in the infectious group, 25 had culture-positive infections of which 13/25 were gram-positive organisms and 12/25 grew gram-negative bacilli. Based on the ROC curve, the sensitivity of D-lactate was found to be 80% and specificity 100% and a cut-off value of above 47.06 ng/µl for D-lactate was defined as positive or true infectious in vitreous samples for diagnosis of endophthalmitis. In-vivo, a mouse model of bacterial endophthalmitis showed the significant production of D-lactate levels in retina and vitreous. Interestingly the levels were elevated in Gram-negative infections compared to Gram-positive bacterial endophthalmitis. Conclusion : Our clinical and in-vivo mouse model data showed that vitreous fluid D-lactate could be used as a bacterial-specific biomarker in the diagnosis of most infectious endophthalmitis and could be implemented for the evaluation of treatment success.